Chapman quick reference captain's guide nautical facts at a glance (Hearst Books, 2003)
Capturing the fundamentals for boaters, this book covers various things from distress on the high seas to navigation aids. It provides the rules of the road for right of way, how to determine the risk of a collision, and what constitutes the danger zone when two boats come close.